algebra 11 - Steve, Tuesday, November 20, 2012 at 10:38am
Apparently you mean that M is the slope. Most folks use lower-case letters.
In any case, we have
2y = -(k+1)x + 6
y = -(k+1)/2 x + 3
The slope is -(k+1)/2
-(k+1)/2 = k-2
-(k+1) = 2k - 2
-k-1 = 2k-2
3k = 1
k = 1/3
algebra 11 - Steve, Tuesday, November 20, 2012 at 10:40am
-(k+1) = 2k - 4
-k-1 = 2k-4
algebra 11 - Agni, Thursday, January 26, 2017 at 4:33pm
Steve, You made another mistake in that second edit.
Once you reach -k-1=2k-4.
You need to subtract 2k from the right side.
That gets you -3k-1=-4.
You add 1 to get rid of that negative one which gets -3k=-3. Solve for k=1